Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1167/iovs.61.2.22
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Aberrations and Axial Elongation in Myopic Children Treated With Orthokeratology

Abstract: Citation: Lau JK, Vincent SJ, Cheung S-W, Cho P. Higher-order aberrations and axial elongation in myopic children treated with orthokeratology. Invest Ophthalmol Vis Sci. 2020;61(2):22. https://doi.org/10.1167/iovs. 61.2.22 PURPOSE. This retrospective longitudinal study aimed to examine the relationship between ocular higher-order aberrations (HOA) and axial eye growth in young myopic children undergoing orthokeratology (ortho-k) treatment. METHODS.Axial length and ocular HOA, measured under cycloplegia ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 59 publications
2
76
1
1
Order By: Relevance
“…In eyes experiencing chronic deprivation of form vision through ocular conditions such as ptosis [12,13], congenital cataract [14], corneal opacity [15], and vitreous haemorrhage [16], abnormal ocular growth is often observed. Similarly, manipulation of retinal image focus through optical treatment strategies such as bifocal or multifocal spectacles [17,18], soft multifocal contact lenses [19,20], or orthokeratology [21][22][23][24] have been linked with reduced progression of axial myopia in children. Investigations in human eyes have also shown a bi-directional response to short-term imposed continuous myopic and hyperopic defocus in children [25] and adults [26][27][28][29][30][31], with a small magnitude axial length reduction associated with rapid choroidal thickening in response to myopic defocus and axial elongation associated with rapid choroidal thinning in response to hyperopic defocus.…”
Section: Introductionmentioning
confidence: 99%
“…In eyes experiencing chronic deprivation of form vision through ocular conditions such as ptosis [12,13], congenital cataract [14], corneal opacity [15], and vitreous haemorrhage [16], abnormal ocular growth is often observed. Similarly, manipulation of retinal image focus through optical treatment strategies such as bifocal or multifocal spectacles [17,18], soft multifocal contact lenses [19,20], or orthokeratology [21][22][23][24] have been linked with reduced progression of axial myopia in children. Investigations in human eyes have also shown a bi-directional response to short-term imposed continuous myopic and hyperopic defocus in children [25] and adults [26][27][28][29][30][31], with a small magnitude axial length reduction associated with rapid choroidal thickening in response to myopic defocus and axial elongation associated with rapid choroidal thinning in response to hyperopic defocus.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Some authors have also reported a strong association between more positive primary spherical aberration and slower eye growth in both spectacle-wearing children 8 and those treated with orthokeratology. 10 While a significant difference in spherical aberration was observed between the two treatment groups after six months (mean 0.54 µm more positive primary spherical aberration in the AOK group), the magnitude of change in spherical aberration was not associated with the extent of eye growth ( Table 4). With respect to analyses of HOA's and eye growth in children treated with orthokeratology, this is the first study to examine the change in the optics of the eye using the natural pupil diameters rather than a fixed pupil size.…”
Section: Discussionmentioning
confidence: 91%
“…6 Recent longitudinal studies have reported an association between axial elongation with inherent corneal 7 or total ocular HOA's in spectacle-wearing children, 8 as well as the change in total ocular HOA's in children treated with orthokeratology. [9][10][11] These studies have utilised fixed pupil diameters across all participants (4-6 mm) with higher levels of individual Zernike terms, such as primary spherical aberration or coma (or greater HO RMS), associated with less axial eye growth. However, the natural pupil size of individuals may be an important factor in the regulation of eye growth with myopia control interventions, given that greater treatment efficacy has been reported for orthokeratology in children with larger pupil diameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В некоторых работах последних лет повышению СА и комы после ОК-коррекции отводят самостоятельную роль в тормозящем прогрессирование эффекте данного воздействия [79,80]. Но прежде всего повышенный уровень аберраций увеличивает глубину фокусной области, снижая нагрузку на аккомодацию за счет повышения псевдоаккомодации.…”
unclassified